HUBUNGAN RESPONSE TIME DENGAN TINGKAT KEPUASAN PASIEN DI INSTALASI GAWAT DARURAT PUSKESMAS - Tiurmaida Simandalahi; Honesty Diana Morika; Weni Sartiwi; Ratna Indah Sari Dewi (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
Abstract : Response time is indicated as one indicator in the quality assessment of hospitals / health centers in the form of customer satisfaction. The purpose of this study is to determine the relationship between response time and the level of patient satisfaction in the Emergency Department. Type of research: descriptive analytic with cross sectional design carried out in July-August 2018. Population: patients who visited the emergency room Air Amo Health Center, taken by accidental sampling as many as 74 respondents. Instruments used: questionnaires and observation sheets, computerized, and univariate analysis: frequency distribution and bivariate: Chi-Square test with a 95% confidence level. The results obtained 56.8% of respondents were satisfied with nursing services, 70.3% stated response time in the response category. Bivariate analysis found there was a relationship between response time and the level of patient satisfaction (p value 0.039). It was concluded that response time was one of the factors related to patient satisfaction. Suggestions through Puskesmas leaders to always evaluate service management so that Puskesmas service quality is always maintained.Keywords : Patient Satisfaction, Response TimeAbstrak : Respons time diindikasikan sebagai salah satu indikator dalam penilaian mutu pelayanan Puskesmas melalui kepuasan pelanggan. Tujuan penelitian untuk mengetahui hubungan antara respons time dengan Tingkat kepuasan pasien di Instalansi Gawat Darurat. Jenis penelitian: deskriptif analitik dengan desain cross sectional dilaksanakan pada Juli–Agustus 2018. Populasi: pasien yang berkunjung ke IGD Puskesmas Air Amo, diambil secara accidental sampling sebanyak 74 responden. Instrumen yang digunakan: kuesioner dan lembar observasi, diolah secara komputerisasi, dan di analisis secara univariat: distribusi frekuensi dan bivariat: uji Chi-Square dengan derajat kepercayaan 95%. Hasil didapatkan 56,8% responden puas dengan pelayanan keperawatan, 70,3% menyatakan response time pada kategori tanggap. Analisis Bivariat didapatkan ada hubungan antara response time dengan Tingkat Kepuasan Pasien (p value 0.039). Disimpulkan response time merupakan salah faktor yang berhubungan dengan kepuasan pasien. Saran melalui pimpinan puskesmas agar selalu mengevaluasi manajemen pelayanan agar mutu pelayanan Puskesmas selalu terjaga.Kata Kunci : Kepuasan Pasien, Response Time